Analysis of Lyrics and Visuals of Good Faith Forever (2023) Live Music Performance - Gunawidjaja, Andrea Rebecca; Mutiaz, Intan Rizky (ULTIMART Jurnal Komunikasi Visual, 2024)
As time and technology advances, visualization in music becomes an important role to support the music performance. Good Faith Forever is a live music performance released in 2021, created and performed by Hugo Pierre Leclercq, and is one of the examples of a unique live music performance, by making a narrative with a different perspective from the lyrics itself by blending the music and visuals together, making it an interesting subject to analyze. The objective of this research is to uncover the relationship between the lyrics and visuals of a live music performance of Good Faith Forever in 2023 as a study case. This research uses an interpretative qualitative approach using Roland Barthes’ Semiotics Theory and Geoffrey Leech’s Semantics Theory to analyze the visuals and lyrics. From the 2023 live performance of Good Faith Forever “The Prince” and “Neo Finale”, it is found that the lyrics and the performance tell the same stories but with different focuses, the lyrics itself focuses on the message of story, while the performance focuses on the narrative and characters living in the message of the lyrics. This implies the existence of creative freedom in interpreting the lyrics to form a similar story for the live performance. Keywords: good faith forever; live music performance; lyrics; music visualization; narratives